Hot stamping of ultra high strength steels as a key technology for lightweight construction - Lechler, Jürgen; Merklein, Marion (Tagungsband Material Science & Technology Conference MS&T’08, 2008)
Due to increased usage of high strength steels in scope of lightweight construction design in this context thermal assistant forming technologies like hot stamping of boron-manganese steels of the type 22MnB5 obtained more and more industrial relevance in the last five years. For a reliable process design the knowledge of the material properties in dependency of the process influencing characteristics and hereby mainly the temperature displays a base requirement. In the following publication an overview will be given about different experimental methodologies developed at the Chair of Manufacturing technology for being capable to investigate the material behavior according to the typical time-temperature profile of hot stamping. Furthermore, main experimental results acquired regarding the thermal, the mechanical and the tribological properties of 22MnB5 will be exemplarily shown as well. © 2008 MS&T'08 ®.
LFT Import::2019-08-05 (1550)
Keywords: 22MnB5; Hot stamping; Material properties; Modeling